MECHANISM OF CASTING OF MATERIALS BY METHOD OF THIXOCOMPACTING - N. K. Tolochko; Ju. A. Shienok (Литьë и металлургия)
There is experimentally investigated the evolution of the structure at casting of materials in hard-liquid state by method of thixocompacting by the example of fusible systems. There are determined the temporary dependencies of the particles diameters, distances between their centers and porosity under different conditions of the process (sizes and space distribution of the particles of basic material, temperature regimes, the compacting pressure).